Pattern of acute poisoning in teaching hospital, northwest Ethiopia - Adinew, Getnet Mequanint; Asrie, Assefa Belay (International Journal of Pharmacology and Toxicology, 2016)
Background: Acute poisoning is considered a major health problem worldwide and is a frequent cause of hospital admission. It is estimated that poisons are responsible for more than 1 million illnesses worldwide annually.Objective: To evaluate retrospectively the pattern of acute poisoning in teaching hospital, northwest Ethiopia.Materials and methods: This was an observational, retrospective study. The study population includes all patients who visiting Gondar teaching hospital emergency room who were diagnosed with acute poisoning from September 2010 to December 2014. All data were analyzed using SPSS 20.Result: Acute poisoning cases constituted 0.67% of the 34320 admissions to the emergency department. Of these 233 patients, 148 (63.5%) were female and 85 (36.5%) were male.88.42% were younger than 30 years of age and the frequency of acute poisoning declined with advanced age. Organophosphates were the most frequent cause of poisoning and accounted for 89 cases (38.2%). Intentional poisoning comprised 57.5 %.83.6 %( 195 cases) of the cases were ingested orally, the mean arrival time to the emergency unit after poisoning was 4.2 hours and the average duration of hospital stay was 11.26hours. It was found that 60 % of the cases were simply received supportive therapy. The most common factors contributing to intentional poisoning was quarreled with their family (54.2%) followed by love affairs (18.4%). The mortality rate was 0.43%Conclusions: The data observed in this hospital based shows acute poisoning remains a major public health problem with pesticide poisoning remaining the most common and therefore concerning poison.